Elements of dream interpretation: laying the foundation of a basic model for clinical practice - Schön, Joan (Rhodes University, Faculty of Humanities, Department of Psychology, 2001)
The study addresses certain paradoxes evident in the theory and practice of dream interpretation. These relate to the considerable value afforded to dreams in psychoanalytic thinking, compared with (1) the surprising dearth of literature, research, and training on dream interpretation in clinical practice, (2) the difficulties voiced by clinicians regarding dream interpretation, and (3) the diversity of keys employed by different schools to unlock the 'truth' of dreams. The intention of the study is to examine these paradoxes in order to develop a model fordream interpretation which falls within the ambit of psychodynamic psychotherapy. It is argued that there have been few insights over the century to match the seminal work of Freud (1900/1976), except perhaps the work of Carl Jung. As a result of the 1914 rift between these two, Jung's insights have been largely ignored in mainstream psychoanalytic thinking and the focus on dreams has given way to other areas of development, such as, unconscious thinking, symbol formation, and interpretation in a general sense. These, it is argued, have contributed to a more comprehensive understanding of dreams and their interpretation. Thus a model would need to consider both Freud and Jung's work, and later salient developments. It would also need to be informed by local, contemporary practice. The method used in this thesis is one of breaking down the process of dream interpretation into component parts, in order to examine useful contributions from different sources and to compare work with dreams to work with other material. The literature review examines the major theoretical contributions in relation to four elements of dreams interpretation: the nature and function of dreams, methods of dream interpretation, the meaning of dreams, and the goals of dream interpretation. A model which accommodates diverse theories without resorting to eclecticism is then proposed. Dream interpretation is further examined in the light of a multiphase clinical study, designed to provide different perspectives on the topic. The study yielded findingscompatible with the literature reviewed, as well as certain problems in relation to the proposed model. These included shortcomings of the elements used in the literature review, particularly the sequence of these elements, and caveats about affording dreams a special focus in the consulting room. Thus a second configuration was posited, namely the idea of viewing dream-work as a triangular situation, comprising the dream, the dreamer, and the dream interpreter. The final model which is the outcome of the study provides two interrelated methods of addressing dream interpretation which accommodate the theory/practice dichotomy. In the first, the elements of dreams and their interpretation are considered sequentially. This method provides a framework for considering theoretical contributions on dreams, as well as issues of technique, without recourse to the introduction of theory in the consulting room. In the second, dream interpretation is regarded as a triangular situation, comprising the interchange between therapist and patient in relation to the patient's dream-life. This structure accommodates the alliance which is discernible in practice and draws on Segal's (1957/1986) notion that the process of symbol formation is a triangular situation. The value of regarding 'dream-work' in the consulting room as a triangular situation is threefold: (1) it is akin to symbol formation in terms of the meaning reached; (2) dreams cannot be accurately interpreted in isolation from the contributions of both therapist and patient; and (3) it provides 'dream-work' in practice with its own structure, highlighting a perspective that dreams are an element of clinical practice, rather than a focus, a subtext within the broader framework of psychodynamic psychotherapy.
Keywords: Dream interpretation; Dreams